Medical tourism in Thailand : A cross-cultural study of medical tourists' decision-making factors - Sasithorn Sonpiam (Prince of Songkla University., 2016)
Thesis (M.B.A., (Hospitality and Tourism Management (International Program))--Prince of Songkla University, 2012